2021
DOI: 10.1158/2159-8290.cd-20-1554
|View full text |Cite
|
Sign up to set email alerts
|

CDK4/6 Inhibition Promotes Antitumor Immunity through the Induction of T-cell Memory

Abstract: The Johnstone laboratory receives research support from Roche, BMS, Astra-Zeneca and MecRx. RWJ is a scientific consultant and shareholder in MecRx. The McArthur laboratory receives non-financial support from Pfizer Oncology for supply of palbociclib.Research.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
59
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 75 publications
(59 citation statements)
references
References 61 publications
0
59
0
Order By: Relevance
“…The previous success of immunotherapy based on anti-cytotoxic TL-associated antigen 4 or anti-programmed death-1/programmed death ligand-1 antibodies confirms the relevance of TL-based anti-tumor immunity and suggests that restoration of the immune system could promote tumor control (31). Several animal and in vitro models have demonstrated the immune actions of CDK4/6i (32)(33)(34). CDK4/6i increase the immunogenicity of tumor cells (32) and enhance tumor infiltration via TL activation (35,36).…”
Section: Discussionmentioning
confidence: 86%
“…The previous success of immunotherapy based on anti-cytotoxic TL-associated antigen 4 or anti-programmed death-1/programmed death ligand-1 antibodies confirms the relevance of TL-based anti-tumor immunity and suggests that restoration of the immune system could promote tumor control (31). Several animal and in vitro models have demonstrated the immune actions of CDK4/6i (32)(33)(34). CDK4/6i increase the immunogenicity of tumor cells (32) and enhance tumor infiltration via TL activation (35,36).…”
Section: Discussionmentioning
confidence: 86%
“…Studies in our laboratory have shown encouraging in vivo anti-melanoma activity of palbociclib in combination with BRAF-MEKi [ 15 , 16 ]. Additional pre-clinical studies also demonstrate potential immuno-modulation by CDK4/6 inhibitors (CDK4/6i) in breast cancer and melanoma with upregulation of MHC Class I expression, T regulatory cell reduction, increased IFN-γ release in the tumor microenvironment and enhanced long-term anti-tumor immunity [ 17 , 18 , 19 , 20 , 21 ].…”
Section: Introductionmentioning
confidence: 99%
“…However, post expansion phase, cells that have been previously exposed to the inhibitors produce a greater pool of memory T cells by upregulating Max Dimerization Protein (Mxd)4, a negative regulator of Myc/Max formation (Heckler et al, 2021). Interestingly, this event seems to be independent of cell cycle arrest, suggesting a role for CDK4/6 in affecting T cell development (Heckler et al, 2021;Lelliott et al, 2021).…”
Section: Expansion Phase (Il-2 Driven Proliferation)mentioning
confidence: 99%
“…There is a 3-fold increase in cyclin D2, and 8-fold increase in cyclin D3, and around a 30-fold increase in CDK4/6 copies, while p27 decreases 19-fold. Interestingly, CD8 + T cells can bypass CDK4/6 inhibition (Goel et al, 2017), leading to slowed proliferation (Heckler et al, 2021;Lelliott et al, 2021), but not arrest. The major changes observed copies in the Rb-E2F pathway may contribute to this resistance to G1 arrest by CDK4/6 inhibitors.…”
Section: The Cell Cycle Control Protein Network In T Cellsmentioning
confidence: 99%